2021
DOI: 10.3390/ani11030703
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Responses and Performance of Dairy Calves Fed Different Amounts of Colostrum

Abstract: This study investigates the newborn thermoregulatory responses to cold and the performance of calves fed different colostrum volumes. Thirty newborn Holstein calves were blocked by birth body weight (BW; 39.4 ± 6.5 kg) and fed different high-quality colostrum volumes: 10%, 15%, or 20% of BW, which was split and fed at 2 and 8 h after birth. At 24 h of life, calves were placed in a chamber at 10 °C for 150 min. Skin and rectal temperature (RT), heart and respiratory rate, and shivering were measured every 15 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…These three elements also provide neonates to energy (48). These factors could explain the significantly lower temperatures on days 0, 1, and 2, suggesting a compensatory effect of colostrum ingestion that, in a study of newborn Holstein calves, brought about an increase of ∼1 • C in prescapular temperature (49). The differences found in the days after birth support the hypothesis that colostrum consumption is essential for newborn ruminants to achieve thermoregulatory success (1).…”
Section: E Ect Of Weight On the Thermoregulation Of Bu Alo Calvesmentioning
confidence: 67%
“…These three elements also provide neonates to energy (48). These factors could explain the significantly lower temperatures on days 0, 1, and 2, suggesting a compensatory effect of colostrum ingestion that, in a study of newborn Holstein calves, brought about an increase of ∼1 • C in prescapular temperature (49). The differences found in the days after birth support the hypothesis that colostrum consumption is essential for newborn ruminants to achieve thermoregulatory success (1).…”
Section: E Ect Of Weight On the Thermoregulation Of Bu Alo Calvesmentioning
confidence: 67%
“…This occurs thanks to the increased plasma triglyceride levels that BAT metabolizes. This effect was explored by Silva et al ( 103 ), who observed that male Holstein calves that consumed an amount of colostrum equivalent to 15 to 20% of their body weight presented less shivering than those that received only 10%. This finding confirms that the metabolic thermogenic response is additional and long-term in nature, though authors like Clarke et al ( 63 ) have stated that the response degree depends on exposure to cold.…”
Section: Thermoregulation Mechanisms To Combat Hypothermia In Ruminantsmentioning
confidence: 99%
“…As the first meal for newborn calves, colostrum has a vital role in calf nutrition and immune defense, growth and development ( Playford and Weiser, 2021 ). The immune status of calves after birth directly depends on the amount and quality of colostrum they consume ( Silva et al, 2021 ). Colostrum quality significantly affects the formation of intestinal microbiota and the daily weight gain of calves, which is the highest when the colostrum density is > 1.070 g/cm 3 ( Puppel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%